2001
DOI: 10.1164/ajrccm.164.6.2007062
|View full text |Cite
|
Sign up to set email alerts
|

Lung Tissue Mechanics and Extracellular Matrix Remodeling in Acute Lung Injury

Abstract: elastance; collagen fibers; elastin; paraquat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 34 publications
10
117
0
9
Order By: Relevance
“…Using an i.p. injection of paraquat model of lung injury in rats, investigators have demonstrated that altered tissue mechanics associated with markers of ECM remodelling are detected as early as 24 h after injury [65]. In another animal study, pulmonary mechanics were assessed in mice with lung injury induced by administration of LPS (either 125 mg i.p.…”
Section: Mmps In Repair Of the Alveolar Epithelial-endothelial Unitmentioning
confidence: 99%
“…Using an i.p. injection of paraquat model of lung injury in rats, investigators have demonstrated that altered tissue mechanics associated with markers of ECM remodelling are detected as early as 24 h after injury [65]. In another animal study, pulmonary mechanics were assessed in mice with lung injury induced by administration of LPS (either 125 mg i.p.…”
Section: Mmps In Repair Of the Alveolar Epithelial-endothelial Unitmentioning
confidence: 99%
“…Exposure to paraquat generates physiological characteristics of acute lung injury (ALI) (Rocco et al, 2001). Collagen and other elastic components are increased in the ALI process due to a fibroelastosis process initiated early in the first 24 h of lesion evolution (Rocco et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to paraquat generates physiological characteristics of acute lung injury (ALI) (Rocco et al, 2001). Collagen and other elastic components are increased in the ALI process due to a fibroelastosis process initiated early in the first 24 h of lesion evolution (Rocco et al, 2001). Exposure to paraquat can significantly induce the expression of connective tissue growth factor, which results in a process of pulmonary fibrosis (Huang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The components of the ECM can be divided into four broad categories: collagen, non-collagenous glycoproteins (such as fibronectin and laminin), glycosaminoglycans and proteoglycans (PTGs), and elastic fibers (48,51,52). Cells continuously remodel their microenvironment by changing the components and structure of the ECM (52,53).…”
Section: Stretch-induced Extracellular Matrix Expressionmentioning
confidence: 99%